Pengaruh Persiapan Gentle Birth terhadap Derajat Kecemasan Ibu Hamil Pertama dalam Menghadapi Persalinan - Novita Wulandari; Sri Achadi Nugraheni; Martini Martini (Jurnal Manajemen Kesehatan Indonesia, 2020)
Pregnancy and childbirth services are needed to provide comfort to reduce the level of anxiety in facing labour among pregnant women. Gentle birth is a method of childbirth that is calm, gentle, polite, and utilizes all natural elements in the human body. This study aimed to determine the effect of Gentle Birth preparation on the level of anxiety in facing labor among primigravidae pregnant women.This study was a quasi experimental with Pre-test – Post-test Control Group Design conducted to 90 pregnant women. The samples were selected using the Purposive Sampling technique, 45 were assigned to the intervention group and 45 were assigned to the control group. Data collected with structured questionnaire. Data analysed with paired t test to determine differences in scores between before and after intervention and independent t test to determine differences in the level of anxiety between groups.The results showed that there was no difference in the level of anxiety before the administration of Gentle birth preparation between the intervention group and the control group (p>0.05), there was a difference in the level of anxiety after the administration of Gentle birth preparation between the intervention group and the control group (p<0.05). The difference can be seen from the decrease in the difference between anxiety scores after the administration of Gentle birth preparation in the intervention group which decreased by -11.4, while in the control group it decreased by -2.13. It can be concluded that there was an effect of Gentle Birth the preparation on the level of anxiety in facing labor among primigravidae pregnant women